Virtual Reality in Medical Education, Healthcare Education, and Nursing Education: An Overview - Georgios Lampropoulos; Antonio del Bosque; Pablo Fernández-Arias; Diego Vergara (Multimodal Technologies and Interaction)
Virtual reality is increasingly used in health sciences education, including healthcare, nursing, and medical education. Hence, this study provides an overview of the use of virtual reality within healthcare education, nursing education, and medical education through the analysis of published documents from 2010 to 2025. Based on the outcomes of this study, virtual reality emerged as an effective educational tool that can support students and health professionals. The immersive, realistic, and safe environments created in virtual reality allowed learners to enhance their knowledge and practice their skills, patient interactions, and decision-making without risking patient safety. Improvements in learning outcomes, including performance, clinical skills development, critical thinking, and knowledge acquisition were observed. Virtual reality also positively contributes toward a more holistic health sciences education as it increases students’ empathy and behavioral understanding. Finally, eight main research topics were identified and research gaps and future research directions are presented.